2016
DOI: 10.3354/dao03015
|View full text |Cite
|
Sign up to set email alerts
|

External injuries of Morelet’s crocodile Crocodylus moreletii in Campeche, Mexico

Abstract: Analysis of external injuries in captive and free-ranging Morelet's crocodiles Crocodylus moreletii was performed in the northern wetlands of Campeche, Mexico. From March to September of 2007, a total of 52 free-ranging and 51 captive Morelet's crocodiles were studied. Captive crocodiles presented significantly more injuries. Sixteen free-ranging crocodiles presented some type of lesion, mostly superficial abrasions. Nineteen captive crocodiles presented lesions, mostly incisions from agonistic interactions. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…territory or females in the breeding season (Cott, 1961;Huchzermeyer, 2003;Grigg & Kirshner, 2015;Padilla & Weber, 2016). Injuries may also be higher in waterbodies where crocodilian-human interactions are higher, with fatal consequences for local crocodilian populations (Pooley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…territory or females in the breeding season (Cott, 1961;Huchzermeyer, 2003;Grigg & Kirshner, 2015;Padilla & Weber, 2016). Injuries may also be higher in waterbodies where crocodilian-human interactions are higher, with fatal consequences for local crocodilian populations (Pooley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We found that injuries were more frequent in males than females but unrelated to anthropogenic waterbodies or higher human disturbance. Prevalence of injuries may relate to density‐dependent factors through social interactions, such as crowding, hierarchy and territory, where males usually engage in disputes for territory or females in the breeding season (Cott, 1961; Huchzermeyer, 2003; Grigg & Kirshner, 2015; Padilla & Weber, 2016). Injuries may also be higher in waterbodies where crocodilian–human interactions are higher, with fatal consequences for local crocodilian populations (Pooley et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%